The Effect of Industrial Work Practices on Vocational Students Self-Efficacy - Hidayati, Ika Novia Nur; Rijanto, Tri; Munoto, Munoto; Nurlaela, Lutfiyah (International Journal for Educational and Vocational Studies, 2020)
Education in SMK if harmonized with the business world and industry world (BW/IW) is a synergistic relationship that greatly supports improving the quality of education in SMK, producing graduates who will be used by BW/IW. Industrial work practice is a stage of professional preparation in which a student studies in the industrial world for a certain period of time. Self-efficacy is a child's natural need to think highly of himself. The first conclusion produced was the implementation of the apprenticeship to meet the needs of workers in accordance with the field, the collaboration between the school and the industrial world, the readiness of student knowledge and good communication between the school and the business world. After that the aspect of the evaluation in the apprenticeship program is a change in student scores when tested, a positive response from the industrial world and an evaluation of the guidance of the assistant teacher internship. Secondly, self-efficacy has a positive effect on prakerin in vocational student entrepreneurship activities.